Head Injury as a Risk Factor for Dementia and Alzheimer's Disease: A Systematic Review and Meta-Analysis of 32 Observational Studies. - Yanjun Li; Yongming Li; Xiaotao Li; Shuang Zhang; Jincheng Zhao; Xiaofeng Zhu; Guozhong Tian (PLoS ONE)
Background Head injury is reported to be associated with increased risks of dementia and Alzheimer's disease (AD) in many but not all the epidemiological studies. We conducted a systematic review and meta-analysis to estimate the relative effect of head injury on dementia and AD risks. Methods Relevant cohort and case-control studies published between Jan 1, 1990, and Mar 31, 2015 were searched in PubMed, Web of Science, Scopus, and ScienceDirect. We used the random-effect model in this meta-analysis to take into account heterogeneity among studies. Results Data from 32 studies, representing 2,013,197 individuals, 13,866 dementia events and 8,166 AD events, were included in the analysis. Overall, the pooled relative risk (RR) estimates showed that head injury significantly increased the risks of any dementia (RR = 1.63, 95% CI 1.34-1.99) and AD (RR = 1.51, 95% CI 1.26-1.80), with no evidence of publication bias. However, when considering the status of unconsciousness, head injury with loss of consciousness did not show significant association with dementia (RR = 0.92, 95% CI 0.67-1.27) and AD (RR = 1.49, 95% CI 0.91-2.43). Additionally, this positive association did not reach statistical significance in female participants. Conclusions The findings from this meta-analysis indicate that head injury is associated with increased risks of dementia and AD.